A Study on Awareness of Various Non-Technical Training Programmes Conducted by Corporate Trainers for IT Companies in Ahmedabad - Chandni J. Vidani; Vrunda Patel; Nilesh Chaudhary (International Journal of Managemen Analytics (IJMA), 2023)
This research aims to investigate the awareness levels among IT professionals in Ahmedabad regarding non-technical training programs conducted by corporate trainers. The study focuses specifically on IT companies in Ahmedabad, a prominent hub for the IT industry in India. The research examines the awareness levels among IT professionals regarding the availability and benefits of non-technical training programs offered by corporate trainers. The questionnaire will assess the participants' awareness levels of non-technical training programs, including their knowledge of the programs offered, their perceived importance, and their willingness to participate. Data collected from the survey will be analyzed to identify the level of awareness among IT professionals and explore any gaps or discrepancies in their knowledge. The findings of this research will provide insights into the current state of awareness regarding non-technical training programs in the IT industry in Ahmedabad. The results will be beneficial for both corporate trainers and IT companies in understanding the existing levels of awareness and the potential for improving the promotion and utilization of non-technical training programs. Additionally, the study will contribute to bridging the gap between the availability of non-technical training programs and the awareness among IT professionals, ultimately fostering their continuous learning and professional growth